The Relationship Between The Level of Maternal Knowledge, Maternal Employment Status and Family Support With Exclusive Breastfeeding in The Working Area of The Air Dingin Health Center of Padang City in 2018 - Dian Hidayah Putri; Masrul Masrul; Lisma Evareny (Faculty of Medicine, Universitas Andalas, 2018)
In order to reduce infant morbidity and mortality, UNICEF and WHO recommend exclusive breastfeeding for six months because ASI has many health benefits for babies and contains all the nutrients needed by baby. The lowest coverage of exclusive breastfeeding in Padang City is in the working area of Puskesmas Air Dingin. The purpose of this study was to determine the relationship between the level of maternal knowledge, maternal employment status and family support with exclusive breastfeeding in the working area of the Air Dingin Health Center. Analytic research withdesign was cross sectionalconducted in the working area of Air Dingin Health Center from June 2018 to July 2018. The sample in this study were mothers who had infants aged> 6-12 months as many as 56 people. Mothers as respondents were interviewed directly using a questionnaire. Data analysis was univariate and bivariate usinganalysis chisquare (p 5 0.05). The results showed that the percentage of exclusive breastfeeding was 51.8%. Theanalysis results chi-square showed that the p value between exclusive breastfeeding and the level of maternal knowledge (p = 0.010), maternal employment status (p = 1,000), and family support (p = 0.021). There was a significant relationship between the level of mother's knowledge and family support with exclusive breastfeeding, while the mother's employment status did not have a significant relationship with exclusive breastfeeding. It is hoped that mothers can maintain and improve exclusive breastfeeding.